Transformational leadership, business intelligence, and e-government: Enhancing public sector performance mediated by risk management - Amrie Firmansyah; Lutfi Abdul Khakim (Badan Pemeriksa Keuangan Republik Indonesia, 2025)
Public sector organizations face increasing pressure to improve performance, accountability, and service delivery amid increasing complexity and uncertainty. While transformational leadership, business intelligence (BI), and e-government have been independently associated with performance improvement, their combined impact—particularly through the mediating role of risk management—remains underexplored. This study investigates the influence of transformational leadership, BI, and e-government on organizational performance in the public sector, with risk management as a mediating variable. Using empirical data from the Ministry of Finance in Indonesia, the study examines how these factors collectively enhance performance by fostering a risk-aware culture, promoting data-driven decision-making, and streamlining administrative processes through digital integration. Partial least squares structural equation modeling (PLS-SEM) was employed to test the model. The findings reveal that transformational leadership, BI, and e-government each exert both direct and indirect positive effects on organizational performance, with risk management acting as a key mediating mechanism. The novelty of this study lies in its integrated framework, which connects leadership, technology, and risk governance in explaining public sector performance. It contributes to the limited literature on risk management in the public sector. It presents practical insights for policymakers seeking to optimize governance frameworks through effective leadership and technological solutions.